Comparative study of in-vitro antioxidant and antidiabetic activity of plant extracts of Acacia arabica, Murraya koeingii, Catharanthus roseus and Rouwolfia serpentina” - Keshaw Ram Aadil; Anand Barapatre; Namrata Rathore; Sandhya Pottam; Harit Jha (International Journal of Phytomedicine, 2012)
Medicinal plants play very important role in preventing the progress of disease. In present studyfour different medicinal plants, Acacia arabica, Murraya koeingii, Catharanthus roseus and Rouwolfia serpentina commonly found in Chhattisgarh, (India), were screened for the potency of antioxidant and antidiabetic activity. Methanolic and aqueous extracts of A. arabica and M. koeingii, C. roseus and R. serpentina plant leaves were examined. Total phenolic content of extracts was analyzed by Folin-ciocalteu’s method. Antioxidant activities of different extracts were evaluated by DPPH and H2O2 scavenging assay and putative Antidiabetic activity was determined by in-vitro glucose diffusion and alpha-amylase inhibition assay. The highest DPPH scavenging activity was found in methanolic extract of C. roseus while the highest hydrogen peroxide scavenging activity was found in aqueous extract of M. koeingii. In in-vitro antidiabetic test, highest α-amylase inhibition was found in methanolic extract of R. serpentina and the highest diffusion rate of glucose was found in aqueous extract of R. serpentina. The plant extracts were further characterized by Liquid chromatography mass spectroscopy. The results suggest that these plants could serve as a source of natural antioxidants and antidiabetic agents with potential applications in pharmaceuticals industry.